(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In today’s increasingly globalized and digital world, the ability to communicate effectively across cultures has become an essential skill. Traditional language learning methods often fall short in developing learners’ real-life communication skills, especially in intercultural contexts. Virtual exchange programs online collaborations between students from different countries offer a powerful solution. This article explores how technology-enhanced collaborative learning through virtual exchange improves students’ communication skills, fosters intercultural competence, and prepares them for global interaction. Drawing on educational theory and practical classroom experience, the paper outlines the benefits, challenges, and effective strategies for implementing such programs [1][2].